2020
DOI: 10.1093/rb/rbaa041
|View full text |Cite
|
Sign up to set email alerts
|

In vitro genotoxicity evaluation and metabolic study of residual glutaraldehyde in animal-derived biomaterials

Abstract: Glutaraldehyde (GA) is an important additive that is mainly used in animal-derived biomaterials to improve their mechanical and antimicrobial capacities. However, GA chemical toxicity and the metabolic mechanism remain relatively unknown. Therefore, residual GA has always been a major health risk consideration for animal-derived medical devices. In this study, extracts of three bio-patches were tested via the GA determination test and mouse lymphoma assay (MLA). The results showed that dissolved GA was a poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…The number of live cells and ALP activity of SHEDs cultured in glutaraldehyde was significantly less when compared to control. These facts were further confirmed by the study conducted by Bhandi and co-workers 28 .Shi J observed that the presence of glutaraldehyde in mouse lymphoma cells could cause considerable cytotoxic and mutagenic consequences 36 .…”
Section: Discussionsupporting
confidence: 52%
“…The number of live cells and ALP activity of SHEDs cultured in glutaraldehyde was significantly less when compared to control. These facts were further confirmed by the study conducted by Bhandi and co-workers 28 .Shi J observed that the presence of glutaraldehyde in mouse lymphoma cells could cause considerable cytotoxic and mutagenic consequences 36 .…”
Section: Discussionsupporting
confidence: 52%
“…Collagen cross-linking increases stiffness and tensile stress, however, it comes with a reduced biocompatibility and possible toxicity of remnant cross-linking agents. [100][101][102] For these types of solutions, the main challenge is finding a reasonable balance between mechanostability and biocompatibility during the first months after implantation, so that residing keratocytes are able to effectively re-establish a healthy ECM.…”
Section: Compositementioning
confidence: 99%
“…Hence, it is not ideal for the production of engineered corneal implants. [100,101] An alternative is genipin, a chemical cross-linker of natural origin that can form both inter-and intramolecular cross-links in collagen fibrils. in vitro, genipin has shown to be a successful cross-linker in collagen type I hydrogels, increasing storage and loss moduli by a factor of 15 and 4.5, respectively.…”
Section: Collagen Cross-linkingmentioning
confidence: 99%
“…In the USA, the biosafety of medical devices is strictly supervised by the Food and Drug Administration [ 16 ]. Currently, biocompatibility evaluations play an important role in the preclinical research stage of hemostatic sponges [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%